¿Qué hace usted? (2020)
¿Qué hace usted? is a podcast that documents jobs in the city of Bogotá. This project has the purpose of narrating, through profiles and sound chronicles, the labor activities of the city, which contribute to the construction and reconstruction of subjectivities and identities (De la Garza, sf). Due to the pandemic of the Covid-19 virus and the quarantine established by the National Government in decree 457 of 2020, two stories of jobs that were exempted from this measure will be told. How is this work done? What was it like during the strict quarantine? How did the quarantine affect this work? These are some of the questions that will be explored in order to build a sound narrative of how these jobs worked in an empty Bogota.